2017
DOI: 10.1002/2017jb014360
|View full text |Cite
|
Sign up to set email alerts
|

JTRF2014, the JPL Kalman filter and smoother realization of the International Terrestrial Reference System

Abstract: We present and discuss JTRF2014, the Terrestrial Reference Frame (TRF) the Jet Propulsion Laboratory constructed by combining space‐geodetic inputs from very long baseline interferometry (VLBI), satellite laser ranging (SLR), Global Navigation Satellite Systems (GNSS), and Doppler orbitography and radiopositioning integrated by satellite submitted for the realization of ITRF2014. Determined through a Kalman filter and Rauch‐Tung‐Striebel smoother assimilating position observations, Earth orientation parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 99 publications
0
24
1
Order By: Relevance
“…Another realization of ITRS is the JTRF2014 developed by Jet Propulsion Laboratory (JPL) based upon the Kalman filter and smoother algorithms (Wu et al 2015, Abbondanza et al 2017. This is a subsecular, time-series based terrestrial reference frame whose origin is at the quasi-instantaneous CM as detected by the SLR technique.…”
Section: Definition Of the Geocenter Motionmentioning
confidence: 99%
“…Another realization of ITRS is the JTRF2014 developed by Jet Propulsion Laboratory (JPL) based upon the Kalman filter and smoother algorithms (Wu et al 2015, Abbondanza et al 2017. This is a subsecular, time-series based terrestrial reference frame whose origin is at the quasi-instantaneous CM as detected by the SLR technique.…”
Section: Definition Of the Geocenter Motionmentioning
confidence: 99%
“…These solutions are derived from the analysis of Doppler Orbitography and Radiopositioning Integrated by Satellite (DORIS), Global Positioning System (GPS), satellite laser ranging (SLR), and very long-baseline interferometry (VLBI) observations. Three new recently released ITRS realizations are ITRF2014 (Altamimi et al, 2016), DTRF2014 (Seitz et al, 2016), and JTRF2014 (Abbondanza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based upon a Kalman filter and smoother algorithm (Soja et al 2016), the JPL team adopts a state vector formulation including position-related variables, Helmert transformation parameters from each individual observing space-geodetic network to the final combined frame and daily EOPs, assimilates the pseudo-observations of position derived from the four space-geodetic techniques at a weekly resolution along with daily EOPs and, when available, site tie observations and realizes a sub-secular TRF (JTRF2014, (Abbondanza et al 2017)) whose origin is at the quasi-instantaneous CM as detected by SLR, whose scale is the weighted average of the quasi-instantaneous scales materialized by fortnightly/weekly SLR and quasi-daily VLBI sessions and whose orientation is defined via application of weekly no-net-rotation (NNR) conditions with respect to ITRF2008.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters and their representation in technique-specific pseudo-observation equation As for the introduction of LTs,(Abbondanza et al 2017) indicated that local tie vectors were applied only once at the epoch of their measurements (as stated in the input SINEX files) for the realization of JTRF2014. For the realization of both ITRF2014 and DTRF2014, the pseudoobservations for the selected LTs were introduced once for the final inter-technique combination.…”
mentioning
confidence: 99%